The Social Science of Hayek's The Sensory Order. - Butos, William N. (Advances in Austrian Economics, 13., 2010)
Fifteen original papers by economists and social theorists examine the relevance and significance of Hayek's cognitive psychology for social science. Papers examine Hayek's cognitive psychology from the perspective of evolutionary theory, economics, market and social institutions, and broader social theory.